Analysis for the Formulation Of A Project for the Management of Cybersecurity Governance for the Optimization of Resources in an Organization - Durango, Rodrigo Del Pozo; Toapanta T, Moisés; Gómez D, Zharayth; Pavón, Pamela Toapanta; Llumiquinga A, Roció; Orizaga T, Antonio; Maciel A, Roció (Journal of Ecohumanism, 2025)
Persistent Challenges in Cybersecurity Governance Project Formulation: A Case Study in Ecuador and Beyond. The formulation of projects aimed at managing cybersecurity governance to optimize organizational resources presents persistent challenges both in Ecuador and globally. Among the most prevalent issues are: A lack of knowledge in identifying relevant standards and policies, Insufficient human resources with expertise and training in cybersecurity, and Deficiencies in norms, prototypes, and appropriate project management models for cybersecurity governance. The objective of this research is to perform the analysis for the formulation of a project for managing cybersecurity governance to optimize resources in an organization. A deductive approach and exploratory research methods were employed to analyze relevant documents and literature. Key Findings: Indicators to support the formulation of cybersecurity governance projects, Proposed solutions for project formulation in cybersecurity governance, Identification of relevant stakeholders essential for project development and resource optimization, Algorithm development utilizing flowchart techniques for project formulation. Conclusions: Simulation results, evaluated through the Likert scale and expert judgment, revealed varying levels of satisfaction: Scenarios 1 and 3: Satisfaction below 75% – indicating dissatisfaction, Scenarios 2 and 4: Satisfaction between 76% and 94% – indicating satisfaction, Scenario 5: Satisfaction between 95% and 100% – indicating high satisfaction. It is concluded that to ensure successful project formulation, all key stakeholders must achieve satisfaction levels exceeding 75%.